Postpandemic Outlook for Higher Education is Bleakest for the Poorest - Altbach, Philip; de Wit, Hans (International Higher Education, 2020)
COVID-19 is creating a broadbased crisis for higher education globally. The implications include challenges to the internationalization of higher education—a key global element in recent decades, financial challenges, and others. Students and academic institutions in low-income countries and in less affluent parts of other nations will be especially affected.